Moral Obligation, Social Values Creation, and Self Efficacy: Determining Factors for the Success of Madurese Sociopreneurs in Halal Branding of MSMEs - Haryanto, Rudy; Purnamawati, Anni Muslimah; Anwar, Moh. Muhlis; Anis, Moh; Suaidi, Suaidi; Sufyan, Akhmad Farid Mawardi (El-Qist: Journal of Islamic Economics and Business (JIEB), 2026)
Background: Despite Indonesia’s mandatory Halal Product Assurance policy, halal branding adoption among micro, small, and medium enterprises (MSMEs) remains uneven, particularly in culturally embedded regions such as Madura. Existing studies predominantly explain halal adoption through regulatory and attitudinal frameworks, offering limited insight into the roles of internal ethical motivation and perceived entrepreneurial capability. Anchored in Social Cognitive Theory. Objective: This study investigates the structural relationships among moral obligation, social value creation, self-efficacy, and the implementation of halal branding. A quantitative cross-sectional survey was conducted across four regencies in Madura. Methodology: Using the Lemeshow sampling formula to determine a representative sample of MSME actors. Data were collected by the Authors through structured Likert-scale instruments and analyzed using Structural Equation Modeling (SEM). Construct validity and reliability were established before hypothesis testing, and the structural model demonstrated acceptable goodness-of-fit indices. Findings: The findings reveal that moral obligation and the creation of social value significantly enhance entrepreneurial self-efficacy. All three variables exert positive and significant effects on halal branding implementation, with self-efficacy partially mediating the influence of ethical and social orientation on branding adoption. These results indicate that halal branding is driven not solely by regulatory compliance but by the interaction between moral conviction, community-oriented value creation, and cognitive confidence. Conclusion: This study advances halal entrepreneurship literature by integrating ethical motivation and sociopreneurial values within a capability-based behavioral framework, offering empirical insights to strengthen sustainable halal ecosystem development in emerging regional economies.